Parental involvement and Special Educational Needs in inclusive contexts - Felizardo, Sara (2017)
Problem Statement: This study aims to analyze the relationships between the parent`s perspectives of children with Special Educational Needs/ SEN and teachers of regular and special education, about parental involvement in school. Research Questions: Are there significant differences between the parent`s perspectives of children with SEN and teachers of regular and special education, in relation to parental involvement in school? Purpose of Study: Parental involvement is a multifaceted concept that encompasses different contexts and can be presented in various formats. Within the inclusive approach, the collaborative model and partnership of parental involvement provides a frame of reference that can help support professionals, educators and teachers in their contacts with parents of children with SEN. Research Methods: This is an descriptive-correlational research with a non-probability convenience sample of 256 parents of children with and without SEN, and 107 teachers of regular and special education. The study was undertaken in schools and institutions of support for disabled children of the Municipality of Viseu, and data were collected with a questionnaire about parental involvement in school. Findings: Data shows that the largest divergence about parental involvement perceptions occurs between the teachers of the regular school and parents of students with SEN. In contrast, the perceptions between teachers of special education and parents of children with SEN do not show significant differences. There are still significant differences between regular teachers and special education teachers about parental involvement in school. Conclusions: Data suggests differences between perceptions of regular education teachers and parents of children with SEN, likewise the perceptions between the two type of teachers, which indicate that the work should evolve towards greater convergence and articulation, in order to delineate forms of intervention converging and promote a greater parental involvement as part of a collaborative and partnership approach.